FEATURE ULTRASONIC DIAGNOSTICS IN INTESTINAL MALROTATION (literature review) (World Bulletin of Public Health, 2024)
Clinical signs in some disorders often lead to a long diagnostic search. The recognition of knowledge in the fie ld of pathology can provide a key to the interpretation of instrumental research methods. The reviews present modern methods o f visualization of the abdominal cavity with intestinal malrotation. It is shown that echographic visualization is a sufficient basis fo r determining operational tactics.